Biochemical Parameters of Laboratory Animals in Iraq: A Meta-analysis Study - A Hussein, Ahmed; O Dahl, Mohammad; G Mustafa, Nashaat (The Iraqi Journal of Veterinary Medicine, 2024)
Our objective in this work was to estimate normal values of biochemical parameters in laboratory animals in Iraq. Values were pooled from studies conducted in Iraqi universities using a meta-analysis approach. Pertinent peer-reviewed published studies were retrieved from the Iraqi Academic Scientific Journals (IASJ) database. Random-effects inverse-variance model was used to obtain pooled means of the parameters from the set of studies qualified for the analysis. Among a total of 460 records identified from IASJ, 264 records were eligible for the statistical analysis, which reported 102 values for different biochemical parameters. The mean of the sample size for normal animals that was used in the studies including in the analysis were 8, 8, and 6 for rats, mice, and rabbits respectively. The mean ± standard deviation of ages (months) was 2.8 ± 1.0, 3.14 ± 1.15, and 9.2 ± 3.3 for rats, mice, and rabbits respectively. In this analysis, we estimated 31, 14, and 15 parameters from 121, 41, and 26 studies of rats, mice, and rabbits correspondingly. The proportion of variance in the parameters for the analyzed studies due to heterogeneity was significant. Evidence of bias in the estimated values due to small studies was found in some parameters. In conclusion, we encourage researchers to consider the values we provided in this analysis and report details of the sample size, number of animals in each group, sex, exact age, and the accurate units for the estimated values in their studies to facilitate further analyses for more reference values in further analyses‎‎‎.